Intelligent connectivity : AI, IoT, and 5G - Yarali, Abdulrahman (Wiley, 2022)
"This book focuses on the fusion between the core technologies of the future ? Artificial Intelligence (AI), 5G, and the Internet of Things (IoT), exploring how they can be mutually supportive. AI, IoT, and 5G are the pillars that lead digital transformation, and the combination of super-fast 5th generation networks with AI and IoT will usher in a new age of intelligent connectivity, particularly beneficial to transportation, logistics, education, healthcare, entertainment, public safety/security and industrial and manufacturing operations. The book will offer technical and economic insights about intelligent connectivity as a key part of transformation in the 4th industrial revolution. The reader (technical and non-technical) will benefit from a comprehensive discussion of Artificial Intelligence, 5G, IoT and machine-learning and how they are vital in the period of open-source programming and moderate cloud computing"- Resumé vydavatel